Enhancing cognitive-motor recovery in Rett syndrome: effects of integrated intervention on neuropsychological and motor outcome - Fabio, Rosa Angela; Semino, Martina; Perina, Michela (Frontiers in Psychology, 2025)
Cognitive-motor integration plays a crucial role in the rehabilitation of individuals with complex disabilities, where dissociated impairments in cognition and movement often hinder global functioning. In this study, we investigated the efficacy of an integrated neurorehabilitation program targeting both neuropsychological and motor domains in patients with Rett Syndrome. Baseline assessments included measures of attention, memory, and temporal sequencing, as well as gross, fine, and graphomotor abilities, evaluated using relevant GAIRS subscales (Global Assessment and Intervention Rating Scale). Nineteen patients were enrolled in an experimental group receiving specialized cognitive-motor training three times a week for two consecutive 5-week periods. A control group of 15 patients participated in standard educational activities without specific cognitive-motor intervention. Performance was evaluated at three time points: T0 (baseline), T1 (after 5 weeks), and T2 (after an additional 5 weeks). Results indicated significant improvements in both neuropsychological and motor functions in the experimental group, with gains observed at both T1 and T2. Notably, a strong and significant correlation emerged between improvements in motor and cognitive measures, underscoring the interdependence of these domains in neurodevelopmental conditions such as Rett Syndrome. These findings support the implementation of integrated cognitive-motor protocols in neurorehabilitation and highlight the value of synchronized interventions to foster global functioning in individuals with complex neurodevelopmental profiles.